The biology of particles (Lewis Publishers, 1994)
The Biology of Particles in Aquatic Systems, Second Edition presents the latest information on particulate and dissolved matter found in aquatic habitats ranging from small streams to oceans. Only by studying this matter can we gain an understanding of the functioning of aquatic ecosystems and thus be able to predict changes that may occur as these systems become stressed. Updated and extensively revised, this new edition covers such topics as classification of particulate and dissolved matter, origin and formation of particles aquatic systems, factors affecting particle aggregation, methods for capturing particles by benthic and planktonic animals, and the use of particulate and dissolved organic matter as food.